Pengenalan Canva Sebagai Media Promosi Lingkungan Hidup di SMP-IT Bina Masyarakat Mandiri - Lita Karlitasari; Gustian Rama Putra; Arie Qur'ania; Irma Anggraeni; M. Iqbal Suriansyah; Boldson H. Situmorang; Agus Ismangil; Dinar Munggaran Akhmad; Siska Andriani; Mulyati Mulyati; Erniyati Erniyati (Universitas Teknokrat Indonesia, 2023)
This Community Service activity is entitled Introduction to Canva as a Media for Environmental Promotion, which is carried out in a partner environment, namely Tepadu Islamic Junior High School Bina Masyarakat Mandiri (BMM IT Middle School). The purpose of this PkM activity is to provide partners with knowledge about using Canva as a medium for promoting the environment, encourage school members to plant medicinal plants in the school environment and be able to use them in an effort to create an environmentally friendly school as well as establishing cooperation between the Computer Science Study Program, Faculty of Mathematics and Natural Sciences, Unpak and SMP IT BMM.